Economic Approaches to Human Labour: From the Labour Theory of Value to the Marginal Productivity of Labour - Martins, Nuno Miguel Ornelas (2015)
A most prominent economic framework, certainly very influential in policy circles, is the idea of a labour market, in which wages are set according to the demand for labour, which depends upon the marginal productivity of labour, and the supply of labour, which depends upon how subjective preferences lead to a given trade-off between consumption and leisure. This analytical framework, which leads to the conclusion that an efficient allocation of labour requires sufficient flexibility in the labour market, contrasts sharply with the approach to human labour of the early classical political economists, who studied value not in terms of supply and demand curves, but rather in terms of the cost of production, expressed in terms of human labour. Here I will discuss these two alternative approaches to human labour, taking into account the methodological and theoretical consistency of each approach, its empirical validity, and the implications that each framework has for economic policy making and the construction of political discourse.